2008
DOI: 10.1210/jc.2008-0714
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lipid and Heparin Infusion-Induced Elevation in Free Fatty Acids and Triglycerides Modifies Circulating Androgen Levels in Women: A Randomized, Controlled Trial

Abstract: The mechanism of iv lipid and heparin infusion-induced elevation of circulating androgens described here might contribute to the development of hyperandrogenism in women with PCOS and suggests that lowering of hyperlipidemia might be a potential therapeutic target in patients with PCOS to treat hyperandrogenemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 34 publications
2
32
1
Order By: Relevance
“…Accumulation of plasma fatty acids in muscle and liver tissues induce mitochondrial dysfunction, oxidative stress, inflammation and immune disorders [84]. On the other hand, high circulating FFA levels have been shown in vivo to increase the production of all androgens in normal women [85]. Another study found that male rats fed on a high monounsaturated fatty acid (MUFA) diet for 6 weeks display increased testosterone levels (vs. low MUFA diet), and that free fatty acid with different degree of saturation increased testosterone levels to significantly different extent [86].…”
Section: Cellular Mechanisms Of Metabolic Insulin Resistance-mostmentioning
confidence: 99%
“…Accumulation of plasma fatty acids in muscle and liver tissues induce mitochondrial dysfunction, oxidative stress, inflammation and immune disorders [84]. On the other hand, high circulating FFA levels have been shown in vivo to increase the production of all androgens in normal women [85]. Another study found that male rats fed on a high monounsaturated fatty acid (MUFA) diet for 6 weeks display increased testosterone levels (vs. low MUFA diet), and that free fatty acid with different degree of saturation increased testosterone levels to significantly different extent [86].…”
Section: Cellular Mechanisms Of Metabolic Insulin Resistance-mostmentioning
confidence: 99%
“…A controlled, ­randomized, crossover trial has shown an increase in adrenal androgen precursors DHEA, DHEAS, ­androstenedione, and in androgens testosterone and 5α-dihydrotestosterone during lipid infusion in healthy young women [37]; this effect appears to be independent of subsequent changes in insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of NEFA overexposure on androgen production has been investigated in vivo and in vitro (8 -10). Indeed, it has been shown that increasing NEFA levels experimentally in normal young men and women, using an Lipovenös/heparin infusion, significantly increased androgen levels (8,9), well before any apparent increase in circulating insulin levels. Using bovine adrenal androgen-secreting cells, we recently published that addition of palmitate, a saturated fatty acid, to the cell culture medium significantly increased ACTH-or forskolin-stimulated androgen production (10).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that metabolic factors contribute more to PCOS hyperandrogenemia than ACTH or LH. Interestingly, lipotoxicity, referring to the cellular adverse consequences of nonesterified fatty acids (NEFA) (6), has been implicated in the development of IR (7), and recent studies have found that increasing circulating NEFA levels also stimulates androgen production in healthy men (8) and women (9). This suggests that systemic NEFA overflow can also trigger androgen production in vivo.…”
mentioning
confidence: 99%